AKIBAT KOREKSI YANG TIDAK TEPAT PADA PASIEN YANG MENGALAMI KELAINAN REFRAKSI MIOPIA DI SUPER OPTIKAL PADANG - Rina Novalinda (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
This scientific paper discusses the Effects of Improper Correction on Patients Who Have Myopia Refraction Abnormalities in Super Optical Padang. This study aims to: (1) Determine the consequences of improper correction in patients with myopia refractive disorders. (2) Knowing how to handle from improper correction in patients with myopia refractive disorders. This type of research is quantitative descriptive. The population in this study were all patients with refraction to myopia during the study. Sampling in this study is the total sampling technique. Data was collected through a questionnaire, then the data were discussed in accordance with the theories proposed in the literature review. The results of the study proved that respondents felt the result of improper correction in patients experiencing myopia refractive abnormalities, then 5 respondents or 16.7% did a good handling of improper corrections, 25 respondents or 83.3% did not make good handling of improper correction.